THE EFFECT OF THE PREDICT-OBSERVE-EXPLAIN (POE) METHOD ON REMOVING THE PRE-SERVICE ELEMENTARY SCHOOL TEACHERS’ MISCONCEPTIONS ABOUT HEAT AND TEMPERATURE - Mustafa İLHAN (Fırat University, 2019)
In this study, the effect of laboratory research activities conducted by the POE method on removing the misconceptions about heat and temperature was investigated. For the purpose of the study, study was carried out by pretest-posttest control group experimental model. 83 students enrolled elementary school teaching program in 2010-2011 academic year second semester were included in the study. While POE method was used in experimental group consisting 42 students, verification laboratory approach was used in control group consisting 41 students. Applications took place between March 28, 2011 and April 24, 2011 for four weeks. The data of the study was collected by Misconceptions Test developed by Gümüş, Öner, Kara, Orbay and Yaman (2003). According to results of the study, POE method is more effective on removing pre-service Elementary School Teachers’ misconceptions about heat and temperature by analogy with verification laboratory approach.